Análise quantitativa de eventos extremos de precipitação da região Leste e Norte de Santa Catarina - Silva, Gilson Carlos da (2011)
The time-variation feature of extreme precipitation events (those can result in flooding) on east and north regions of the Santa Catarina State, one of the Brazilian regions most attained by damages owning to heavy rain episodes, is analyzed in this study. For this, it were selected some cities whose history of flooding based on many sources, as the Defesa Civil Estadual was employed to built a threshold to identify the precipitation events that can cause flooding. The observed precipitation data, from 1951 to 2010, from ANA (Agência Nacional de Águas) was used to the analysis of daily rainfall occurred until fifteen days before the flooding and for the counting of this type of event. The methodology employed to detect these events was based on mean thresholds following the rainfall observed on the selected cities. The counting of the occurrences generated the time-variation over such period, indicating positive and also some negative, although not significant tendencies on this region, and a significative linear correlation with global scale climate phenomena in some of the cities. It is also observed the seasonal behavior for the present time and for a future climate scenario, ranging from 2070 to 2100, which aim is to give information to a better planning of the cities, through the regional climate model HadRM3P, from Hadley Centre (UK), simulated and provided by CCST (Centro de Ciências do Sistema Terrestre) do INPE (Instituto Nacional de Pesquisas Espaciais), considering the A2 scenario (more pessimist) following IPCC (Intergovernmental Panel on Climate Change). In comparison against present climate, the estimated projection by climatic model shows an increasing of the frequency of these extreme precipitation events in all selected cities, for all seasons mainly in autumn.